Fecal fungal microbiota alterations associated with clinical phenotypes in Crohn’s disease in southwest China - Zeng,Li; Feng,Zhe; Zhuo,Ma; Wen,Zhonghui; Zhu,Cairong; Tang,Chengwei; Liu,Ling; Wang,Yufang (PeerJ, 2022)
Although previous studies reported that gut fungal microbiota was associated with Crohn’s disease (CD), only a few studies have focused on the correlation between gut fungi and clinical phenotypes of CD. Here, we aimed to analyze the association between intestinal fungi and the occurrence of CD, disease activity, biological behaviors, and perianal lesions. Stool samples from subjects meeting the inclusion and exclusion criteria were collected for running internal transcribed spacer 2 (ITS2) high-throughput sequencing. Then, correlation analysis was conducted between intestinal fungi and different clinical groups. There were 45 patients with CD and 17 healthy controls (HCs) enrolled. Results showed that two phyla, Rozellomycota and Mortierellomycota, were not present in patients with CD compared to HCs. At the same time, there was a higher abundance of fungal genera and species belonging to the phylum Ascomycota in patients with CD. SparCC network analysis showed fewer interactions among the fungal communities in patients with CD compared to HCs. Exophiala dermatitidis was positively associated with the clinical active stage and platelet count. The genus Candida was with significantly higher abundance in the non-B1 CD group based on the Montreal classification. Clonostachys, Humicola, and Lophiostoma were significantly enriched in patients with CD with perianal lesions. Our results demonstrated that the composition of the intestinal fungal microbiota in patients with CD and HCs was markedly different, some of which might play a pathogenic role in the occurrence of CD and perianal lesions. Exophiala dermatitidis and genus Candida might be associated with active disease stage and type non-B1 CD (CD with intestinal stenosis or penetrating lesions, or both), respectively.
Keywords: Crohn’s disease; Clinical phenotypes; Fecal fungal microbiota